Obesity and secondary sexual maturity in boys - Modella Rahmani Femina; Madarina Julia; Soeroyo Machfudz (Indonesian Pediatric Society Publishing House, 2013)
Background Obesity induces earlier secondary sexual maturity in girls. However, results of studies in boys have been inconclusive. Objective To assess for an association between obesity and sexual maturity in boys. Methods This was a prospective cohort study on 133 obese and 133 matched-for-age, non-obese, prepubertal boys, aged 9 to 10 years. They were observed every 4 months for a two year period. Obesity was defined as the BMI ≥the 95th percentile, according to the Centers for Disease Control 2000 growth charts. Secondary sexual maturity was defined as testicular volume of ≥4 mL and Tanner staging of pubic hair of ≥P2. Two trained nurses and a pediatric resident collected the data. Results By the end of the study period, 106 (79.7%) obese boys had attained a testicular volume of 4 mL or more, vs. 85 (63.9%) non-obese boys (RR 1.78; 95%CI 1.19 to 2.67; P=0.004). Furthermore, 81 (60.9%) obese boys attained pubic hair states of Tanner stage P2 vs. 37 (27.8%) non-obese boys (RR 1.85 95%CI 1.46 to 2.34; P<0.001). The mean durations for achieving testicular volume of ≥4 mL were 21.25 (95%CI 20.75 to 21.74) months in obese boys and 22.26 (95%CI 21.80 to 22.72) months in non-obese boys (P=0.007). The mean durations for achieving Tanner stage P2 were 17.04 (95%CI 16.44 to 17.63) months in obese boys and 20.87 (95%CI 20.05 to 21.68) months in non-obese boys. Conclusion Obesity is associated with earlier onset of sexual maturity in boys.